Here's a question I found while studying functional equations. $f(x+y)=f (x)f (y)$ (for all $x,y$ belonging to the set of real numbers) and $f'(0)=2.$ We have to find $f (x).$

So the method we've been taught in class goes like this

  1. Partially differentiate both sides of functional equation w.r.t. $x$ or $y$ $f'(x+y)=f'(x)f (y)$ (Partial differentiating w.r.t. $x$)

  2. Put $x=0$ to get $f'(y)=f'(0)f (y).$

Now since $f '(0)$ is known, we have a differential equation which we can easily solve to give the answer which comes out to be $f (x)=e^{2x}.$

But I am not getting it why this method works?

Secondly, in the first step while partial differentiating we assumed that $y$ is a constant. But in the second step we are integrating w.r.t. $y.$ This doesn't make sense. How can $y$ be treated as a constant and a variable in a single problem?

  • $\begingroup$ This is the classic homomorphism $x\to e^x$ which can be composed with the continuous bijection $x\to ax$, $a$ constant, giving $x\to e^{ax}$ whose derivative gives $a=2$. $\endgroup$
    – Piquito
    May 30, 2018 at 15:23
  • $\begingroup$ The partial differentation should be $f'(x+y) = f'(x)f(y) + f(x)f'(y) \frac{dy}{dx}$. Assume that y is independent of x, i.e $\frac{dy}{dx}=0$ $\endgroup$ May 30, 2018 at 15:26

2 Answers 2


We have $$f(x+y) = f(x)f(y)$$ Partial differentiate respect to x $$f'(x+y) = f'(x)f(y) + f(x)f'(y) \frac{dy}{dx}$$ Since there is no restriction on x or y. y is independent of x. $\frac{dy}{dx}=0$ $$f'(x+y) = f'(x)f(y)$$ The definition of function is for all x,y it applies the above $\forall x,y$. We can choose any x we want. Since we know $f'(0)$, we choose $x=0$ $$ f'(y) = f'(0)f(y)=2f(y)$$ So, $f'(y)=2f(y)$ solve using seperation of variables $$\frac{df(y)}{dx}=2f(y)$$ $$\frac{df(y)}{f(y)}=2dx$$




This can be solved in the following way. Because $f$ is continues at least at $x=0$, and satisfies Cauchy equation $f(x+y)=f(x)f(y)$, it must be $f(x)=a^x$ or $f(x)=0$, for some $a>0$, but it can't be $f(x)=0$, since $f'(0)=2$. Then $$ f'(x) = a^x\ln(a) $$ and putting $x=0$ $$ f'(0)=2=\ln(a) \implies a=e^2 $$ So we have $$ f(x)=e^{2x} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.